Hymecromone Efficacy in the Treatment of Biliary Pancreatitis - A. V. Okhlobystin; M. A. Tatarkina; O. Z. Okhlobystina; S. A. Budzinskiy; P. V. Pavlov; L. A. Labut (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To study the contribution of biliary sludge (BS) to the development of chronic pancreatitis in patients with gallbladder sludge and verified chronic pancreatitis; to evaluate the clinical efficacy and safety of hymecromone therapy according to clinical and laboratory signs, as well as dynamics of gallbladder size and contractility.Materials and methods. An open single-centre clinical trial included 30 patients with chronic pancreatitis (CP), which was diagnosed according to the Cambridge criteria. All patients received hymocromone (Odeston®) 400 mg tid for 3 weeks. An analysis of the efficacy and safety of the studied drug was performed on the 21st day of treatment based on the results of laboratory tests, abdominal ultrasound, cholecystography and endosonography of the pancreatobiliary zone, quality-of-life assessment according to the SF-36 questionnaire, the frequency and severity of adverse effects (AE).Results. CP signs were found in 6.3 % of patients with gallbladder BS. CP was significantly more frequent in patients with putty-like bile (33.3 %, χ2 = 38.21, p < 0.00001). The area of the major duodenal papilla (MDP) was below normal in 78% of patients. According to factor analysis, monotherapy with hymocromone resulted in a decrease in abdominal pain, nausea, heaviness in the abdomen and bloating. By the end of the therapy, the quality of life according to the “BP” bodily pain scale of the SF-36 questionnaire significantly increased.Conclusions. Biliary sludge (including undiagnosed forms during routine examination) was found to be a factor in the development of CP. The medical correction of biliary disorders in CP should include selective antispasmodics. Hymecromone therapy demonstrates a good level of tolerability and safety, normalizes the motor function of the biliary tract and sphincter tone over a short period of time, and relieves CP symptoms.